THE POSSIBILITY OF PSYCHOLOGICAL SUPPORT OF PERSONALITY IN THE FORMATION OF SUBJECTIVITY STUDENTS - Irina Lilienthal; Inna Kotesnikova (Вестник Северо-Кавказского федерального университета, 2022)
The article covers the basics of psychological support, we propose a model of psychological support to students in the educational process of the university, aimed at the development of their personalization and subjectivity of the individual. Describes the conditions of implementing the ideas of psychological support in educational practice and the advantages of their implementation.